Unusual molecular findings in autosomal recessive spinal muscular atrophy. Issue 6 (June 1996) - Matthijs, G; Schollen, E; Legius, E; Devriendt, K; Goemans, N; Kayserili, H; Apäk, M Y; Cassiman, J J
Abstract : All three types of autosomal recessive spinal muscular atrophy map to chromosome 5q11.2-q13.3 and are associated with deletions or mutations of the SMN (survival motor neurone) gene. The availability of a test to distinguish between the SMN gene and its nearly identical centromeric copy cBCD541 allows molecular diagnosis. We have analysed patients from 24 Belgian and 34 Turkish families for the presence or absence of a deletion in the SMN gene. A homozygous deletion in the SMN gene was seen in 90% of unrelated SMA patients. A non-radioactive SSCP assay allows for a semiquantitative analysis of the copy number of the centromeric and SMN genes. Hence, direct carrier detection has become feasible under certain conditions. We observed a phenotypically normal male, father of an SMA type I patient, presenting with only a single copy of the SMN gene and lacking both copies of the cBCD541 gene. This illustrates that a reduction of the total number of SMN and cBCD541 genes to a single SMN copy is compatible with normal life. In another SMA type I family, there is evidence for a de novo deletion of the centromeric gene in a normal sib. This observation illustrates the susceptibility of the SMA locus to de novo deletions and rearrangements.